A novel alendronate functionalized nanoprobe for simple colorimetric detection of cancer-associated hypercalcemia. Issue 28 (22nd May 2018) - Sahu, Abhishek; Hwang, Youngmin; Vilos, Cristian; Lim, Jong-Min; Kim, Sunghyun; Choi, Won Il; Tae, Giyoong
Abstract : Alendronate conjugated gold nanoparticle was developed as a nanosensor for colorimetric detection of calcium ion in the biological samples. Abstract : The calcium (Ca 2+ ) ion concentration in the blood serum is tightly regulated, and any abnormalities in the level of serum calcium ions are associated with many potentially dangerous diseases. Thus, monitoring of the Ca 2+ ion concentration in the blood serum is of fundamental importance. Gold nanoparticle (GNP)-based colorimetric biosensors have enormous potential in clinical diagnostic applications due to their simplicity, versatility, and unique optical properties. In this study, we have developed an alendronate functionalized gold nanoparticle (GNP-ALD) system for the measurement of Ca 2+ ion concentration in biological samples. The GNP-ALD system showed higher sensitivity towards the Ca 2+ ion compared to adenosine diphosphate (ADP) or adenosine triphosphate (ATP). The strong interaction between the Ca 2+ ion and ALD at the GNP/solution interface resulted in significant aggregation of the ALD conjugated GNPs, and induced a color change of the solution from red to blue, which could be visually observed with the naked eye. The interaction between the Ca 2+ ion and GNP-ALD was characterized by UV-visible spectroscopy, transmission electron microscopy (TEM) imaging, and dynamic light scattering (DLS) analysis. Under the optimized conditions, the lower limit of Ca 2+ ion detection using this method was found to be 25 μM and a linear response range from 25 μM to 300 μM Ca 2+ ions was obtained with excellent discrimination against other metal ions. The GNP-ALD nanoprobe could successfully determine the ionized Ca 2+ concentration in various serum samples and the results were validated using a commercial calcium assay kit. Moreover, as a practical application, we demonstrated the utility of this nanoprobe for the detection of cancer-associated hypercalcemia in a mouse model.